1981
DOI: 10.1055/s-0038-1650121
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Local Anaesthetics and Antiarrhythmic Agents on the Responses of Rabbit Platelets to ADP and Thrombin

Abstract: SummaryLocal anaesthetics and antiarrhythmic agents produced changes in responses of rabbit platelets to ADP and thrombin that varied with the agent and its concentration. In high concentrations all local anaesthetics decreased aggregation rates. At lower concentrations several local anaesthetics increased aggregation rates. Depending on the agonist and local anaesthetic, increases were produced at all or only at low or high agonist concentrations. Local anaesthetics failed to influence shape change except at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…19 On the other hand, it has been shown that cocaine enhances the response of rabbit platelets to arachidonic acid, possibly potentiating thromboxane generation and platelet aggregation. 20 In view of these conflicting reports, a critical analysis of the effect of various concentrations of cocaine on human platelet activation and aggregation is needed.…”
mentioning
confidence: 99%
“…19 On the other hand, it has been shown that cocaine enhances the response of rabbit platelets to arachidonic acid, possibly potentiating thromboxane generation and platelet aggregation. 20 In view of these conflicting reports, a critical analysis of the effect of various concentrations of cocaine on human platelet activation and aggregation is needed.…”
mentioning
confidence: 99%
“…Moreover, these inhibitory properties, in addition to the recognized capability of local anaesthetics to influence the distribution of Ca++ in a variety of tissue membranes [7,20,21] including platelets [1], could also be due to the capability of these drugs, at high doses, to displace Ca++ from the membrane [2] or to block the Ca++ influx into the platelets [1].…”
Section: Discussionmentioning
confidence: 99%
“…Local anaesthetics inhibit platelet aggrega tion and the secretion of contents of platelet storage granules elicited by ADP, thrombin, collagen and the Ca++ ionophore A 23187 [ 1,2]. With regard to cocaine, it has also been demonstrated by O'Brien in 1962 [3,4], Aledort andNiemetz in 1968 [5] and Geerdink et al in 1972 [6] that, at high doses, the drug inhibits rabbit platelet aggregation induced by ADP and thrombin, in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations